Radio Emission from Supernova Remnants: Model Comparison with Observations - Denis A. Leahy; Felicity Merrick; Miroslav Filipović (Universe, 2022)
Supernova remnants (SNRs) are an integral part in studying the properties of the Galaxy and its interstellar medium. For the current work, we compare the observed radio luminosities of SNRs to predictions based on a recent analytic model applied to 54 SNRs with X-ray observations. We use the X-ray data to determine the properties of shock velocities, ages and circumstellar densities for the SNRs, whereas shock radii are determined from catalogs. With this set of SNR properties, we can calculate the model radio emission and compare it to the observed radio emission for a sample of SNRs. This is the first time that this test has been carried out—previously the SNR properties were assumed instead of derived from X-ray data. With the assumption that the radio emission process depends on SNR properties in the form of power-law functions, we explore ways to improve the radio emission model. The main results of this study are (i) the model has significant deficiencies and cannot reproduce observed radio emission; and (ii) the model can be improved significantly by changing its dependence on SNR parameters, although the improved model is still not accurate. Significant work remains to improve the components of radio emission models, including changes to the SNR evolution model, the radio emitting volume, and the efficiencies for conversion of shock energy into relativistic electrons and for magnetic field amplification.